Border Cities and Urban Expansion: The Case of Zarumilla and Aguas Verdes on the Peru-Ecuador Border - MANUEL DAMMERT GUARDIA; VIKTOR BENSÚS (El Colegio de la Frontera Norte, A.C., 2017)
This research analyzes the conurbation process of two Peruvian cities on the border with ecuador: Zarumilla and a guas v erdes. This article studies how dif ferent processes and phe - nomena at local, national, international, and global scales inf luence the socioeconomic dy - namics of borders and shape the urban landscape and residents' ties with cities on the other side of the border. i ntensive f ieldwork involving surveys, interviews, f ield observations, and the use of secondary sources took place as part of the study.